APPRAISING NUTRITION AND CHILD REARING AS AN ANTIDOTE TO PSYCHOLOGICAL WELL-BEING AND CHILD DEVELOPMENT IN NIGERIA - B. A. Akwash, Francis (IJRDO - Journal of Social Science and Humanities Research, 2016)
Optimal nutritional status results when children have access to affordable, diverse, nutrient-rich food; appropriate maternal and child-care practices; adequate health services; and a healthy environment including safe water, sanitation and good hygiene practices. This paper identified psychological theories that are relevant to nutrition and child development, and psychological approaches relevant to the problem of under-nutrition and child development in Nigeria. Availability of resources to the caregiver for its implementation is therefore imperative. These esources include knowledge and beliefs about child rearing, the health and nutritional status of the care provider, control of resources and/or autonomy for child care (these include decision making role and employment of caregiver), workload and time constraints for providing child care and social support (these include availability of alternate caregivers, sharing of workload, father’s role in child care and community support). The growth and nutritional outcomes of children is dependent on a complex relationship between the intrinsic characteristics of the child and the competence of the mother in providing child care.